THE EFFECT OF STRESS ON THE ORGANISM OF THE LAW ENFORCEMENT DURING TRAINING IN EXTREME AND STRESS SITUATIONS - Рогальский, Владимир (SWorldJournal, 2020)
The article considers the concept of stress and its impact on the body of law enforcement in extreme and stressful situations. Personal strategies for overcoming professional stress that affects police officers in the performance of their professional du